2012
DOI: 10.1007/s00128-012-0699-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Metal Concentrations in Sediments from Lake Bafa (Western Anatolia): An Index Analysis Approach

Abstract: Metals, organic carbon contents were determined in surficial and core sediment samples from Lake Bafa, Western Anatolia in 2010. The ranges of Fe, Mn, Pb, Cu, Ni, Cr, Zn and Hg contents of sediments from the Bafa Lake were 9.4-35 g kg(-1), 250-780, 2.3-20, 5.8-55, 1.2-480, 63-278, 26.6-79.9 and 0.013-0.273 mg kg(-1), respectively. The mean metal concentrations in surficial sediments obtained in this study decreased in the following order; Fe > Mn > Ni > Cr > Zn > Cu > Pb > Hg for Bafa lake. Total organic carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…In this study, mean contents of heavy metals in decreasing order were found to be Fe > Mn > Ni > Cr > Zn > Cu > Co > Pb > Cd. These results are in agreement with those of a previous study conducted in the same area 33 . It is also clear that heavy metal concentrations varied spatially, with the highest mean Co, Cu, Mn, Ni, and Zn concentrations on the northern side of the lake (L2), and the highest mean Cd, Cr, and Fe concentrations on the eastern side (L3).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, mean contents of heavy metals in decreasing order were found to be Fe > Mn > Ni > Cr > Zn > Cu > Co > Pb > Cd. These results are in agreement with those of a previous study conducted in the same area 33 . It is also clear that heavy metal concentrations varied spatially, with the highest mean Co, Cu, Mn, Ni, and Zn concentrations on the northern side of the lake (L2), and the highest mean Cd, Cr, and Fe concentrations on the eastern side (L3).…”
Section: Discussionsupporting
confidence: 94%
“…These efforts are increasing the significance of monitoring and assessment, especially in sediments and biota in surface water resources in Turkey. Building on existing literature, a limited number of studies have been undertaken on heavy metal pollution in the sediments of Lake Bafa [33][34][35][36] . Previous studies in the area have generally been focused on spatial changes in heavy metal pollution, and the distribution of heavy metals within the soil structure.…”
mentioning
confidence: 99%
“…Both tectonics and sedimentological processes (N-S extension, graben, horst, erosion, delta progradation) and climate events (both orbital and abrupt changes) have played spectacular roles in modulating the ecological conditions in the Eastern Mediterranean Sea coastal areas. The ecological systems in this region include a variety of terrestrial aquatic ecosystems, ranging from fluvial, lacustrine, and lagoonal to coastal marine environments [6,[47][48][49][50][51][52][53][54][55]. Additional factors affecting the environmental conditions in such systems include abrupt geological events (e.g., storms, earthquakes, and tsunamis) and global fluctuations of sea level changes related to orbital climatic oscillations.…”
Section: Implications For Holocene Age Local Environmental Conditionsmentioning
confidence: 99%
“…Several geological and geomorphological studies have been carried out in and around the Lake Bafa These studies have contributed to our knowledge of the coastal geomorphological history, sea level changes, tectonic processes driven erosion rates, climate and environmental induced changes (vegetation and faunal changes) and human impact [6,8,9,[48][49][50][51][52][53][54][55][56][57].…”
Section: Implications For Holocene Age Local Environmental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation